2012
DOI: 10.1152/ajpendo.00572.2011
|View full text |Cite
|
Sign up to set email alerts
|

Expression of functional TSH receptor in white adipose tissues of hyt/hyt mice induces lipolysis in vivo

Abstract: To determine the relative importance of TSH in white adipose tissue, we compared the adipose phenotypes of two distinct mouse models of hypothyroidism. These models differed in that the normal reciprocal relationship between thyroid hormone and TSH was intact in one and disrupted in the other. One model, thyroidectomized (THYx) mice, had a 100-fold increase in TSH and a normal TSH receptor (TSHR); in contrast, the other model, hyt/hyt mice, had a 120-fold elevation of TSH but a nonfunctional TSHR. Although bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…In the present study, our first finding is that TSH has a negative effect on the proliferation of PMCs, and thus gave a direct evidence for the relationship between the pituitary axis and the skeletal system. This is consistent with the study of Endo et al that high serum TSH contributes to the growth retardation in the affected animals by comparing two distinct mouse models of hypothyroidism with or without a functional TSHR [19]. Our study provides the direct cellular basis underlying the phenotype they observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, our first finding is that TSH has a negative effect on the proliferation of PMCs, and thus gave a direct evidence for the relationship between the pituitary axis and the skeletal system. This is consistent with the study of Endo et al that high serum TSH contributes to the growth retardation in the affected animals by comparing two distinct mouse models of hypothyroidism with or without a functional TSHR [19]. Our study provides the direct cellular basis underlying the phenotype they observed.…”
Section: Discussionsupporting
confidence: 92%
“…However, the role of TSH on non-thyroid tissues is under debate. It was reported that TSH stimulated the proliferation of vascular smooth muscle cells [17] and have a direct role in the progression of atherosclerosis by regulating blood sugar and lipid metabolism [17][18][19]. However, TSH is a negative regulator in bone remodeling by inhibiting osteoclast mediated bone resorption [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid-stimulating hormone (TSH) and the melanocortins (MCs) adrenocorticotrophic hormone (ACTH) and melanocyte-stimulating hormone stimulate AC by activation of the G s -coupled TSH receptor (Laugwitz et al 1996, Endo & Kobayashi 2012) and MC receptors (Cho et al 2005, Rodrigues et al 2013) respectively (Fig. 3).…”
Section: Alternative Regulatory Pathwaysmentioning
confidence: 99%
“…In the complex system of hypothalamic regulation, the factor favoured by most authors when discussing the cause for activation of the thyroid in overweight is activation of hypothalamic centres by leptin released from adipocytes in fat tissue [19,29,30,31]. There is a complex interaction between the thyroid hormones and adipose tissue where TSH and thyroid hormones may participate in adipocyte differentiation [32] and lipolysis regulation [33], whereas various adipocyte cytokines may interact with the hypothalamic-pituitary-thyroid axis [34,35,36]. …”
Section: Obesity and Pituitary-thyroid Activationmentioning
confidence: 99%